Taxing meat - Mosca, Joseph (2020)
A narrative analysis was performed using news articles from Sweden to explore the narratives around taxing meat in Sweden. Online articles published between 01/01/2017 – 31/12/2018 were found using a keyword search for meat tax (köttskatt). Narrative analysis moves the focus from individual meanings towards the larger, societal narratives and in turn how these narratives influence people’s lives. Articles were analysed using the concept of small stories, based on previous work by Michael Bamberg. The study explores which were the key actors of the meat tax discourse identified in the articles and how they were positioned in the small stories in relation to the meat tax topic. A master narrative was identified as anti-tax, farmers being made the victims in the discussion, and proclaiming that Swedish meat is environmentally friendly. Counter to this, there was a counter narrative that is pro-taxation of meat, sceptic to Swedish political will to stand up to industry and economic interests, and critical of Swedish meat and meat consumption. The actors (stakeholders) identified through various small stories as supporting the master narrative in media include farmer associations, and centre-right political groups, while on the other hand, counter narratives seen to be centre-left political groups, and environmental activists. Some actors (Swedish Green Party, Swedish University of Agricultural Sciences) are positioned by storytellers as supporting both counter and master narrative. This is especially true on the issue of defining Swedish meat in its role, whether it is somehow different or not from imported, foreign produced meat. This paper adds to the literature about how meat’s relationship to climate change is discussed in media and explores the opinions, views and attitudes on taxing as a method of climate change resilience. Further research could comparatively study how Swedish media on the topic differs from that of other countries.